2020
DOI: 10.20538/1682-0363-2019-4-92-101
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic potential of gut microbiota in Parkinson’s disease

Abstract: Background. Nowadays many efforts are taken in searching for Parkinson’s disease biomarkers, especially for an early recognition of the disease. The gut microbiota is one of the potential sources of biomarkers, changes in the composition of which in PD are actively studied.The aim of this study is to identify microbiota biomarkers in the Parkinson’s disease with an estimated accuracy of the diagnostics, including differential diagnostics, relative to other neurological diseases for patients of the Russian popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The GI involvement in PD led several groups to analyze the composition of gut microbiota in PD and so far, 11 studies have been published (Table 1) [20][21][22][23][24][25][26][27][28][29][30]. Despite differences in terms of patient recruitment (number and selection criteria) and methods of analysis (molecular biology, bioinformatics and statistics), all these studies identified changes in the composition of the gut microbiota in PD (Table 1).…”
Section: Gut Microbiota In Pdmentioning
confidence: 99%
See 2 more Smart Citations
“…The GI involvement in PD led several groups to analyze the composition of gut microbiota in PD and so far, 11 studies have been published (Table 1) [20][21][22][23][24][25][26][27][28][29][30]. Despite differences in terms of patient recruitment (number and selection criteria) and methods of analysis (molecular biology, bioinformatics and statistics), all these studies identified changes in the composition of the gut microbiota in PD (Table 1).…”
Section: Gut Microbiota In Pdmentioning
confidence: 99%
“…Despite differences in terms of patient recruitment (number and selection criteria) and methods of analysis (molecular biology, bioinformatics and statistics), all these studies identified changes in the composition of the gut microbiota in PD (Table 1). Compared to the control population, an increase of Akkermansia (6 studies) [20][21][22][23][24][25] and Lactobacillus bacteria (5 studies) [20,[25][26][27][28] as well as a decrease of Prevotella bacteria (6 studies) [20,[22][23][24]26,27] was observed in PD patients. The other concordant results between the studies were the lower abundance of Faecalibacterium (4 studies) [22,24,27,29] and Blautia (3 studies) [21,24,29] and an increase in the number of Bifidobacterium (3 studies) [22,24,27].…”
Section: Gut Microbiota In Pdmentioning
confidence: 99%
See 1 more Smart Citation